MANAJEMEN RISIKO PADA PEMBIAYAAN USAHA KECIL DAN MIKRO - Iqbal Fahri Tobing; Muhammad Suhaimi; Zuhrinal M. Nawawi (JURNAL ILMIAH EDUNOMIKA, 2023)
Risk is an effect that cannot be eliminated from business activities but can be minimized by implementing risk management. Risk management is a step to manage the possibility of obstacles that will occur in a company or business. This research is a library research method. Literature research is a data collection technique by examining books, journals, literature, and notes on various reports relating to the problem to be solved. From the results of the research above, it can be seen that the implementation of financing risk management really needs to be implemented on an ongoing basis in line with the increasing risk of financing arrears. Financial institutions (including LKMS) need to be active in reviewing customers or members who are likely to experience loan arrears so that financial institutions can anticipate from the start. Islamic financial institutions must identify the financing risks inherent in all their products and activities.